Congenital or neonatal cytomegalovirus infection?. - Graça, André (2004)
Congenital Cytomegalovirus (CMV) infection occurs in about 1% of the newborns, but it is clinically unapparent in around 90% of the cases during the newborn period. This congenital infection may be the cause of neurological sequelae of variable severity, namely neuro-sensorial hearing loss. In most cases of hearing loss secondary to congenital CMV infection, the newborn was asymptomatic. The diagnosis of congenital CMV infection is made traditionally by culturing the virus from urine during the first three weeks of life. In the present case, the authors describe the situation of a two months old black female infant, admitted for irritability, vomiting and generalized convulsions. During investigation, the authors found lab results in favor of recent CMV infection. The imaging studies performed (cerebral ultrasound scan, computerized tomography and magnetic resonance imaging) were normal. As the infant was older than three weeks, it was not possible to make the diagnosis of congenital CMV infection by a positive urine sample. The diagnosis was made by a positive Polymerase Chain Reaction made on the Guthrie card, collected on the fifth day of life and archived in the national laboratory that centralizes the early diagnosis of phenylketonuria and hypothyroidism. The authors review the epidemiology, diagnosis, prognosis and prevention of the congenital CMV infection, giving a perspective of the magnitude of this disease, its sequelae and the new diagnostic methods available, even when the infection is clinically unapparent on the newborn period.